An oracy assessment toolkit: Linking research and development in the assessment of students' spoken language skills at age 11-12. (April 2017) - Mercer, Neil; Warwick, Paul; Ahmed, Ayesha
Abstract: This article describes the development of a set of research-informed resources for assessing the spoken language skills (oracy) of students aged 11-12. The Cambridge Oracy Assessment Toolkit includes assessment tasks and procedures for use by teachers, together with a unique Skills Framework for identifying the range of skills involved in using talk in any specific social situation. As we explain, no comparable, 'teacher-friendly' instrument of this kind exists. Underpinning its development is the argument that teaching children how to use their first or main language effectively across a range of social contexts should be given higher priorityv in educational policy and school practice, and that the development of robust, practicable ways of assessing oracy will help to achieve that goal. We explain how the Toolkit has been developed and validated with children and teachers in English secondary schools, and discuss its strengths and limitations. Highlights: Evaluation of research-informed resources for assessing spoken language skills. 'Oracy Assessment Toolkit' has assessment tasks and a unique Skills Framework. Review of development, validation, strengths & limitations of Toolkit.